The association between pre-treatment occupational skill level and mood and symptom burden in early-stage, postmenopausal breast cancer survivors during the first year of anastrozole therapy. - Nugent, Bethany; Sereika, Susan; Rosenzweig, Margaret; McCue, Michael; Merriman, John; Bender, Catherine; Nugent, Bethany D; Sereika, Susan M; Merriman, John D; Bender, Catherine M (Supportive Care in Cancer, 2016)
Purpose: Previous research has explored occupational activity of breast cancer survivors but has not examined the influence of occupational level on symptoms prospectively. The purpose of this study was to examine the relationship between occupational classification and changes in mood and symptom burden for postmenopausal breast cancer survivors during the first year of anastrozole therapy.Methods: This was an exploratory secondary analysis in 49 postmenopausal women receiving anastrozole therapy for early-stage breast cancer. Participants reported their occupation at baseline and completed self-report questionnaires measuring mood and symptom burden at baseline, 6 months, and 12 months. Occupation was classified according to four major skill levels delineated by the International Standard Classification of Occupations (ISCO).Results: Breast cancer survivors employed at occupational skill levels 1 through 3 reported significantly higher depressive symptoms, fatigue, and total symptoms on average than those employed at ISCO skill level 4. After adjusting for multiple comparisons, this pattern remained for the musculoskeletal, vasomotor, and gastrointestinal symptom subscales.Conclusions: Breast cancer survivors employed at lower skill levels (i.e., ISCO 1-3) reported poorer mood and greater symptom burden than breast cancer survivors employed at a higher skill level (i.e., ISCO 4). Assessing baseline occupation of occupationally active breast cancer survivors may improve understanding of the association between types of occupations and mood and symptom trajectories and may inform development of interventions to mitigate symptom severity in order to help breast cancer survivors maintain optimal occupational function and adherence to therapy.